Effect of Incorporating Stevia and Moringa in Cookies on Postprandial Glycemia, Appetite, Palatability, and Gastrointestinal Well-Being - Ahmad, J.; Khan, I.; Johnson, Stuart; Alam, I.; Din, Z. (American College of Nutrition, 2017)
© 2017 American College of Nutrition Background: Medicinal plants including stevia and moringa constitute an important source of health-beneficial bioactive components, and hence their intake may beneficially modulate biomarkers of chronic diseases. Objective: The objective of the present study was to investigate the effect of incorporating stevia and moringa leaf powder in cookies on postprandial glycemia, appetite, palatability, and gastrointestinal well-being in humans. Method: In a randomized crossover design, 20 healthy subjects consumed 3 isocaloric test foods (each providing 50 g available carbohydrates) of control cookies (CC) made from 100% wheat flour, cookies containing stevia leaf powder (SC, 3% w/w), and cookies containing moringa leaf powder (MC, 5% w/w) as breakfast. Blood glucose and subjective appetite were measured at fasting and at 15, 30, 45, 60, 90, and 120 min after the consumption of the cookies. Palatability and gastrointestinal well-being were measured using standard questionnaires. Results: Compared to CC, MC resulted in a significant decrease in postprandial blood glucose concentration at 30 and 45 min (p = 0.002 and p = 0.003, respectively) and showed a tendency (p = 0.077) for lower blood glucose incremental area under the curve (iAUC). Subjects were significantly less hungry after SC and MC intake (p = 0.035 and p = 0.041, respectively) compared to CC. All the cookies were liked by the subjects without any reported gastrointestinal discomfort. Conclusion: The results showed that compared to CC, MC improved postprandial glycemia and reduced hunger, while SC reduced hunger only. Future studies are now warranted to explore the mechanisms responsible for these observed effects.